Detoxifying the heavy metals: a multipronged study of tolerance strategies against heavy metals toxicity in plants - Ejaz, Ujala; Khan, Shujaul Mulk; Khalid, Noreen; Ahmad, Zeeshan; Jehangir, Sadia; Fatima Rizvi, Zarrin; Lho, Linda Heejung; Han, Heesup; Raposo, António (Frontiers in Plant Science, 2023)
Heavy metal concentrations exceeding permissible limits threaten human life, plant life, and all other life forms. Different natural and anthropogenic activities emit toxic heavy metals in the soil, air, and water. Plants consume toxic heavy metals from their roots and foliar part inside the plant. Heavy metals may interfere with various aspects of the plants, such as biochemistry, bio-molecules, and physiological processes, which usually translate into morphological and anatomical changes. They use various strategies to deal with the toxic effects of heavy metal contamination. Some of these strategies include restricting heavy metals to the cell wall, vascular sequestration, and synthesis of various biochemical compounds, such as phyto-chelators and organic acids, to bind the free moving heavy metal ions so that the toxic effects are minimized. This review focuses on several aspects of genetics, molecular, and cell signaling levels, which integrate to produce a coordinated response to heavy metal toxicity and interpret the exact strategies behind the tolerance of heavy metals stress. It is suggested that various aspects of some model plant species must be thoroughly studied to comprehend the approaches of heavy metal tolerance to put that knowledge into practical use.